A Challenge in Our Time: Issues of Race in Supply Chain Management. Issue 3 (31st October 2020) - Esper, Terry L.; Goldsby, Thomas J.; Zinn, Walter
Abstract : This editorial addresses one of the greatest challenges of our time—racial inequality. Logistics and supply chain management (SCM) factor prominently in people's everyday experiences, as consumers of products and logistics services as well as through participation in logistics and supply chain workforces. These everyday experiences can be quite disparate depending on one's race. As academics, we have a responsibility to peel back the layers of how these issues of race and diversity impact and interact with supply chain phenomena. This editorial is intended to bolster conversation around these issues. We identify compelling themes that merit consideration and, perhaps, deeper investigation, including race as an individual difference variable in our research, race in SCM talent and leadership, and race and racism in SCM execution. We also call for more research that addresses racial inclusion and equal access in other aspects of SCM in light of its far‐reaching influence in the realms of business and society. The time has come to address these pervasive issues affecting organizations and individuals. We also introduce the articles appearing in the current issue of the journal.